Ambulatory blood pressure correlates wıth mrı-based renal volume ın chıldren and adolescents wıth autosomal domınant polycystıc kıdney dısease - (:unkn) unknown (My University, 2022)
Objective: In adult patients with autosomal dominant polycystic kidney disease (ADPKD) renal volume was found to be significantly greater in hypertensive compared to normotensive patients. The purpose of this study was to find out if blood pressure (BP) is related to renal size also in children with ADPKD, for example, in an early stage of the disease. Method and results: Sixty-two children with ADPKD and normal renal function (mean age 12.3+/-4.3 years) were examined by renal ultrasound and ambulatory BP monitoring (ABPM). Twenty-two children were hypertensive and 40 normotensive. Mean renal volume was significantly greater in hypertensive than in normotensive children (2.7+/-2.3 SDS versus 1.2+/-2.5 SDS, P<0.01) despite similar anthropometric data and renal function. Similarly the mean number of cysts was significantly higher in hypertensive patients than in normotensive (35+/-15 cysts versus 23+/-14 cysts, P<0.01). Renal volume correlated with daytime as well as with night-time systolic and diastolic BP (r=0.41-0.47, P<0.01). Correlations with renal length and the number of renal cysts were somewhat less (r=0.29-0.43, P<0.05 and 0.01, respectively). Conclusions: This study revealed a significant relationship between renal volume, renal length and number of renal cysts and BP. It is suggested that children with ADPKD should regularly be checked for BP changes by ABPM, especially those who show increased renal size or a high number of renal cysts on ultrasound. All these children are at high risk for development of hypertension.
Keywords: Tıp; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; İç Hastalıkları; Nefroloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Child Health and Diseases; Internal Diseases; Nephrology; Health Sciences; PEDİATRİ; Klinik Tıp; Klinik Tıp (MED); ÜROLOJİ VE NEFROLOJİ; PEDIATRICS; CLINICAL MEDICINE; Clinical Medicine (MED); UROLOGY & NEPHROLOGY; Pediatri; Üroloji; Pediatri, Perinatoloji ve Çocuk Sağlığı; Pediatrics; Urology; Pediatrics, Perinatology and Child Health